KOMPASS directory of industry and commerce of Philippines. - Belgosa Business Communications, Inc. (Makati City Belgosa Business Communications, 1996)
Encompassing 15,500 companies from all over the Philippines, KOMPASS volume 1 provides a comprehensive listing of companies, giving information on their locations, contacts, number of employees, date of establishment, and names of executives. Volume 1 also provides an index of companies, presenting the companies' profiles by region and by area. Volume 2 provides a list of products and services of the 15 500 companies listed in volume 1 company profiles. The vol. 2 directory also includes tables showing locations of companies producing the different products and providing the different services.
v.1. Company information -- v.2. Products & services.
Keywords: Industries -- Philippines -- Directories; Philippines -- Commerce -- Directories